Anti-Lung Cancer and Cell Migration Inhibition Properties of Ethyl Acetate Extract of Selaginella doederleinii Towards HTB-183 Cells through In Silico and In Vitro Approach - Amaliyah, Alfiah; Kusumaningtyas, Triana Arum; Febriansah, Rifki (Indonesian Society for Cancer Chemoprevention, 2024)
Continuous research and development to obtain novel anti-lung cancer agents is essential, considering the high prevalence and mortality of the disease. The biflavonoid compounds of Selaginella doederleinii showed significant anticancer activities. This study aims to determine the cytotoxic and cell migration inhibition properties of ethyl acetate extract of Selaginella doederleinii (EAESD) against HTB-183 cells through in silico and in vitro methods. This study started with extraction and then identified biflavonoids in EAESD by HPLC. In vitro analysis was conducted through MTT Assay to observe the cytotoxic properties of EAESD and Wound Scratch Healing Assay to observe its cell migration inhibitory properties. In silico studies to obtain the potential anti-lung cancer compounds and their protein targets were conducted through bioinformatics, combining PASS analysis, Swiss Target Prediction, and STITCH. The obtained compounds and protein targets were analyzed in Molecular Docking to evaluate the binding affinities. The result showed that EAESD contained biflavonoid compounds, exhibited cytotoxic activity with an IC50 value of 190 μg/ml, and inhibited the migration rate of HTB-183 cells. Based on in silico analysis, the three biflavonoids with the highest potential of antilung cancer activity along with their target protein are robustaflavone 7,4-dimethyl ether with EGFR, heveaflavone with ESR1, and 7,4',7'',4'''-tetra-O-methyl-amentoflavonewith TNF. All compounds can bind to each protein target with the docking score -9.2 kcal/mol, -9.5 kcal/mol, and -6.5 kcal/mol, respectively. This study suggested preliminary data regarding the potential of Selaginella doederleinii to inhibit the proliferation and migration of the HTB-183 cell line of lung cancer.Keywords: Selaginella doederleinii, HTB-183, cytotoxicity, cell migration, in silico analysis.